Cross‐cultural adaptation and translation of a quality of life tool for new mothers: a methodological and experiential account from six countries. (19th July 2012) - Symon, Andrew; Nagpal, Jitender; Maniecka‐Bryła, Irena; Nowakowska‐Głąb, Agata; Rashidian, Arash; Khabiri, Roghayeh; Mendes, Isabel; Pinheiro, Ana Karina Bezerra; de, Mirna Fontenele; Wu, Liping
Abstract Aim To examine the challenges and solutions encountered in the translation and cross‐cultural adaptation of an English language quality of life tool in India, China, Iran, Portugal, Brazil, and Poland. Background Those embarking on research involving translation and cross‐cultural adaptation must address certain practical and conceptual issues. These include instrument choice, linguistic factors, and cultural or philosophical differences, which may render an instrument inappropriate, even when expertly translated. Publication bias arises when studies encountering difficulties do not admit to these, or are not published at all. As an educative guide to the potential pitfalls involved in the cross‐cultural adaptation process, this article reports the conceptual, linguistic, and methodological experiences of researchers in six countries, who translated and adapted the Mother‐Generated Index, a quality of life tool originally developed in English. Data sources Principal investigator experience from six stand‐alone studies (two published) ranging from postgraduate research to citywide surveys. Discussion/implications for nursing This analysis of a series of stand‐alone cross‐cultural studies provides lessons about how conceptual issues, such as the uniqueness of perceived quality of life and the experience of new motherhood, can be addressed. This original international approach highlights practical lessons relating to instrument choice, and the resources available to researchers with different levels of experience. Although researchers may be confident of effective translation, conceptual and practical difficulties may be more problematic. Conclusion Instrument choice is crucial. Researchers must negotiate adequate resources for cross‐cultural research, including time, translation facilities, and expert advice about conceptual issues.